Incidence of Photography in the Identification of Professional Journalistic Roles: A Empirical Study in Native Spanish Digital Media News - López del Ramo, Joaquín; Humanes Humanes, María Luisa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The identification of professional journalistic roles through photography and its correlation with the headline is studied. We designed an original coding sheet for content analysis, applied to 602 news items from five native Spanish digital newspapers. There is basic agreement between images and text. The “interventionist” role predominates over the “disseminator”, based on “interpretation”. In the relationships between the journalist and the Powers, the role “watchman” prevails over the “loyal-facilitator”. Subjective photographic techniques are rarely used, in images with low expressiveness. Original proposal due to the lack of work on roles focused on photography.